2012
DOI: 10.1007/s00426-012-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Online prediction of others’ actions: the contribution of the target object, action context and movement kinematics

Abstract: Previous research investigated the contributions of target objects, situational context and movement kinematics to action prediction separately. The current study addresses how these three factors combine in the prediction of observed actions. Participants observed an actor whose movements were constrained by the situational context or not, and object-directed or not. After several steps, participants had to indicate how the action would continue. Experiment 1 shows that predictions were most accurate when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…The remaining 20 infants were excluded because they became excessively fussy early in the experiment ( n = 2), they did not act on the object during execution trials ( n = 1), or they had an insufficient number of trials (less than 3) that were free of movement and EEG artifact in one or more test conditions ( n = 17). This rate of data loss is similar to other studies of the infant mu rhythm involving multiple within-subjects conditions (e.g., Reid, Striano, & Iacoboni, 2011; Stapel, Hunnius, & Bekkering, 2012). …”
Section: Methodssupporting
confidence: 86%
“…The remaining 20 infants were excluded because they became excessively fussy early in the experiment ( n = 2), they did not act on the object during execution trials ( n = 1), or they had an insufficient number of trials (less than 3) that were free of movement and EEG artifact in one or more test conditions ( n = 17). This rate of data loss is similar to other studies of the infant mu rhythm involving multiple within-subjects conditions (e.g., Reid, Striano, & Iacoboni, 2011; Stapel, Hunnius, & Bekkering, 2012). …”
Section: Methodssupporting
confidence: 86%
“…Notably, TMS was delivered at the very same time point in all conditions, that is at the moment of maximum leg extension of the soccer player after kicking the ball, right before the second step (i.e., stopping or continuing to run). This suggests a motor activation in line with the predicted movement (Kilner et al, 2004;Knoblich & Flach, 2001), finely tuned to early cues in the observed actions (Aglioti et al, 2008;Sartori et al, 2011a;Makris & Urgesi, 2014;Stapel, Hunnius, & Bekkering, 2012). Predicting another person's behavior has immediate implications for one's own action selection system because, depending on the output of action simulation, a suitable action can be selected from a multiplicity of possible alternatives (Bekkering et al, 2009;Sartori et al, 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…[71]), observers are better at predicting the outcome of actions [72] and at estimating the duration [73] of motorically familiar actions when they watch them performed by others. Moreover, experienced adults tend to outperform novices when asked to recognize, categorize and recall observed actions [74][75][76][77].…”
Section: (A) Action Experience and Action Understanding In Adultsmentioning
confidence: 99%